Experimental study of physical and rheological properties of grape juice using different temperatures and concentrations. Part I: Cabernet Sauvignon - de Castilhos, Maurício Bonatto Machado [UNESP]; Betiol, Lilian Fachin Leonardo [UNESP]; de Carvalho, Gisandro Reis [UNESP]; Telis-Romero, Javier [UNESP] (Elsevier, 2017)
The effect of the temperature and concentration on rheological behavior of Cabernet Sauvignon juice concentrates was assessed using a rheometer over a wide range of temperature (1–66 °C) and concentrations (13.6–45.0 Brix) at shear rates of 0.84–212.1 1/s. The Ostwald-De Waele was the best rheological model fitted the data (R2 = 0.99957 and relative error = 7.77%). The Cabernet Sauvignon juice concentrates presented a non-Newtonian pseudoplastic behavior (n < 1). The consistency levels were significantly reduced with the increase of temperature and increased with the increase of the concentrations. The flow activation energy ranged from 28.87 (45.0 Brix) to 38.05 KJ/mol (37.0 Brix) with a R2 = 0.9798 for both cases. Density and specific heat were influenced by both temperature and concentration; however, thermal conductivity was only influenced by concentration. The Cabernet Sauvignon juice concentrates will be useful as wine chaptalization agent in future studies.
Keywords: Activation energy; Cabernet Sauvignon; Grape juice; Physical properties; Rheology